Now we should mark that y-z must be >0 because |X| is always postive. (Property of a modulus)

Picking up Statement 1:

Given x + y = z

=> -x = y - z

if x > 0 then y-z < 0 but that does not help us answer the question

if x <= 0 then y - z > 0 we would want that

This statement is not sufficient by itself.

Picking up Statement 2:

x < 0

This statement is not sufficient by itself.

But if we combine both the statements, gives us the answer.

Hence answer is C.

## Please log in or register to add a comment.